Islamic Feminists’ Rejection of the Textual Understanding of Misogynistic Hadiths for the Advancement of Gender Justice in Makassar, Indonesia - Tasbih, Tasbih; Langaji, Abbas; A. Hafid, Saidah; Bakti, Andi Faisal; Haris, Abdul Gaffar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Islam is a religion that upholds the values of justice and equal rights between men and women, but the understanding of the Indonesian Muslim community is still wrong with the teachings of Islam. One of the reasons includes misunderstanding of misogynistic hadiths, namely hadiths that editorially seem to demean women. This study aims to explore Islamic feminists’ rejection of the textual understanding of misogynistic hadiths to uphold gender justice. This Islamic feminist stance needs to receive support so that gender justice is in line with Islamic law. This research uses empirical qualitative methods by analyzing the theory of understanding hadith and gender theory. The study obtained data from interviews and a literature review. The respondents interviewed were academics, NGO activists, and community leaders, while the literature included journal articles, books, and Islamic textbooks on Islamic law. The study took place in Makassar City, Indonesia from September 2022 to March 2023. Findings reveal that Islamic feminists in Makassar City criticize the textual interpretations of misogynistic hadiths as they demean women’s dignity and are not in accordance with the values of Islamic teachings. If analyzed from a gender perspective, Islamic feminists have played an important role in fighting for gender equality in a religious context. Meanwhile, in the context of hadith understanding theory, a contextual approach is needed to provide a comprehensive understanding of society so that gender justice is realized. The contribution of this study is that the Islamic feminist perspective that reviews misogynistic hadith through a contextual approach helps provide inspiration and direction for other efforts to encourage social change and gender justice.